(untitled) (Journal of Hama University, 2025)
In this study, wastewater resulting from Aleppo University Hospital was treated using Syrian crude zeolite by adsorption method. A representative sample of Syrian crude zeolite was collected. The raw zeolite was ground and sorted according to granular size. Samples of wastewater resulting from Aleppo University Hospital were collected and then determined. Their physical and chemical specifications using reference analytical techniques. The treatment of polluted wastewater using adsorption technology using raw zeolite was studied under different treatment conditions (quantity, contact time, granular size). It was found that the effectiveness of the treatment increases with the amount of added zeolite, the best of which is 2 grams per litter of polluted water. It was also shown that the effectiveness of the treatment increases. By decreasing the granular size of the adsorbent material used, as a result of the increase in the specific surface, it was noted that a size of 100 microns is considered the best. The effectiveness of the treatment increases as the contact time (soaking) increases, and the best time is 120 minutes. The results have proven that the treated water is suitable for irrigation